Tree Growth and Forage Production in Block and Canalside Plantations of I.G.N.P. Stage-II - Upadhyaya, A. K. (Indian Forester, 1996)
Based on six monthly observations on four year old canalside and block plantations in command area of Indira Gandhi Canal Project, growth rate and forage production under six species has been discussed. Eucalyptus camaldulensis attained maximum height and collar girth of 12.85 m and 55 cm respectively, whereas, minimum growth was observed in case of Prosopis cineraria which attained a height of 3.87 m and collar girth of 22 cm in four years. However, forage production under Prosopls cineraria was maximum and it was minimum in association with Eucalyptus camaldulensis plantations.